CAFF Technical Report No.4 - Global Overview of the Conservation of Arctic Migratory Breeding Birds Outside the Arctic - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (Conservation of Arctic Flora and Fauna Working Group (CAFF), 1998)
Global Overview of the Conservation of Arctic Migratory Breeding Birds Outside the Arctic is the Arctic Council's CAFF Working Group's Technical Report No.4, published 1998